PERBEDAAN TINGKAT PENGETAHUAN SETELAH PENYULUHAN PLAK MENGGUNAKAN MEDIA VIDEO PEMBELAJARAN DENGAN LEAFLET PADA SISWA SMP (Politeknik Kesehatan Kemenkes Bandung, 2021)
Dental and oral health counseling is an activity that aims to improve, provide examples, to provide warnings about the importance of maintaining dental and oral health. When counseling using media can make it easier when counseling takes place. Media that can be used when counseling include videos and leaflets. The purpose of this study was to determine the media used can provide changes in knowledge of students in grades VIII.This study uses a pre-experimental design with the research method used pre-posttest by looking at the results before and after treatment, namely by looking at the assessment of the results of the pre-posttest given during the counseling. The sampling technique used is purposive sampling with the number of respondents as many as 60 students. This research was conducted on June 3, 2021 using whatsapp and google meet media. The results of the analysis of this study is the average of both groups increased. The average before being given treatment in the group using leaflet media was 79.67, increasing to 91.67, while the average before the study using instructional video media was 76.33, increasing to 88.33. The results of the independent T-test showed that the results of the two media did not show a significant difference (Sig (2-tailed) > 0.05).